Superconductivity: A Centenary Celebration - Dahal, Kul Prasad (Himalayan Physics, 2011)
Superconductivity was empirically discovered 100 years ago. This paper describes briefly the history and developments in critical temperature of different superconductors. Many efforts have been put on research and development so as to raise critical temperature. Different superconducting materials both conventional and unconventional have been discovered. The phenomenon of superconductivity is widely applicable in different fields of S&T so as to ease human life and activities. High - temperature superconductors have taken central stage as a dream material after long research and development. Hitherto, superconductors have proven to be highly varied in composition but elusive and mysterious. Keywords: Centenary of superconductor; Chronological development of Tc; Conventional and unconventional superconductors; High temperature superconductors; Insufficiency of BCS theory The Himalayan Physics Vol.2, No.2, May, 2011 Page: 26-34 Uploaded Date: 1 August, 2011